KOMUNIKASI BISNIS WARUNG SATEKAMBING BU HJ. BEJO LOJIWETAN DALAM MEMPERTAHANKAN BRAND TRUST - Difa Zulfania Nur Fauzi; Andri Astuti Itasari (Solidaritas, 2025)
This study aims to examine the business communication applied by Warung Sate Kambing Bu Hj. Bejo Lojiwetan in maintaining brand trust amidst the competitive culinary industry. It uses a descriptive qualitative approach with David K. Berlo’s SMCR communication model as the analytical framework. Data were gathered through observation, in-depth interviews, and documentation. The findings reveal that verbal and non-verbal communication by the owner and employees play a crucial role in creating positive customer experiences, alongside consistent taste and friendly service. An effective communication approach via diverse channels, including social media, supports consumer loyalty and sustainable brand trust. Effective business communication is the key to successfully maintaining the brand trust of Warung Sate Kambing Bu Hj. Bejo. Keywords: Business Communication, Brand Trust, SMCR Model, Warung Sate Kambing Bu Hj. Bejo Lojiwetan